Gas supply systems. Gas installation pipework with an operating pressure greater than 0, 5 bar for industrial installations and greater than 5 bar for industrial and non-industrial installations. Detailed functional requirements for commissioning, operation and maintenance Part 2, (28th February 2023) - British Standards Institution,
No abstract available